2019
DOI: 10.3389/fnsys.2019.00007
|View full text |Cite
|
Sign up to set email alerts
|

Action Observation With Dual Task for Improving Cognitive Abilities in Parkinson’s Disease: A Pilot Study

Abstract: Action observation therapy (AOT) has been recently proposed as a new rehabilitation approach for treatment of motor deficits in Parkinson’s disease. To date, this approach has never been used to deal with cognitive deficits (e.g., deficits in working memory, attention), which are impairments that are increasingly recognized in Parkinsonian patients. Typically, patients affected by these dysfunctions have difficulty filtering out irrelevant information and tend to lose track of the task goal. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 98 publications
(124 reference statements)
0
15
0
Order By: Relevance
“…Interestingly, action observation therapy has been demonstrated effective in improving cognitive abilities of PwPD if it is used within a dual task framework ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, action observation therapy has been demonstrated effective in improving cognitive abilities of PwPD if it is used within a dual task framework ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…As there is a limited effect of pharmacological therapy or deep brain stimulation on dual-tasking (9), other strategies are sought to positively influence these deficits. Previous studies showed that both, attentional cognitive performance and dual-tasking are responsive to training interventions and have a reciprocal impact on each other (1012).…”
Section: Introductionmentioning
confidence: 99%
“…27 AO is recognized as one of the cognitive training approaches 9,12 that can activate the MNS which is partially damaged in MCI. 6 A recent study of Caligiore et al 15 found improved cognitive domains (working memory and attention) after AO combined with dual-task training for 4 weeks in Parkinson's disease. They proposed an explanation of cognitive improvement through the mechanism of stimulating goal-setting within the MNS by AO and the mechanisms of working memory and goal maintaining by dual-task training.…”
Section: Discussionmentioning
confidence: 98%
“…However, cognitive ability can be gained more through observing complicated tasks or using cues in patients with Parkinson's disease. 15,19 Given the points outlined, AO might be more suitable for use in the elderly with MCI. Therefore, the study aimed to investigate the effect of AO combined with gait training on gait and cognition in elderly with MCI.…”
mentioning
confidence: 99%